The Influence of Work Motivation and Servant Leadership on Job Satisfaction of Civil Servants (ASN) in the Bengkulu Provincial Government (The Manager Review, 2025)
This study aims to investigate how job satisfaction of Bengkulu Provincial Government employees is affected by work motivation and service leadership, as well as to examine the role of work motivation as a moderator. The sampling technique used was simple random sampling, with a total of 350 Bengkulu Provincial Government employees participating in this survey-based study. Data processing was carried out using SEM-PLS. The results of modeling the structural equation show that work motivation and service leadership have a positive and significant effect on job satisfaction. In addition, work motivation was found to positively and significantly moderate the influence of service leadership on job satisfaction with the quasi-moderator type. The findings in this study are expected to provide valuable input for the Bengkulu Provincial Government in formulating strategies and policies that aim to maintain and/or improve things that are considered important to the findings of the research variables, so that they can continue to be able to transform and become better from time to time. Future research should consider contextual factors that may influence the relationships identified in this study.